Heat stress amelioration by astaxanthin supplementation and Nrf2 transcribed downregulation of HSP70 and MnSOD in Karan Fries (Holstein Friesian ×Tharparkar) heifers - KUMAR, SUNIL; SINGH, S V (The Indian Journal of Animal Sciences, 2019)
Karan Fries (Holstein Friesian × Tharparkar) heifers are sensitive to heat stress due to exotic inheritance. Therefore their productive performances are affected adversely under tropical climatic conditions. Hence, the present study was conducted on Karan Fries (10-12 months) heifers by dividing into two group i.e. control (fed as per ICAR, 2013) and treatment group (additionally supplemented with astaxanthin @ 0.25 mg/kgBW/day/animal). Environmental parameters (dry and wet bulb temperature, and relative humidity) were recorded throughout the study and temperature humidity index (THI) was calculated. THI was used to assess the levels of summer stress. Blood samples were collected at fortnightly interval from both the groups of heifers for estimation of oxidative stress markers i.e. antioxidants enzyme (SOD, GPx and catalase). RNA was isolated from collected blood samples for Nrf2, HSP70 and MnSOD gene expression at monthly interval. Plasma catalase, SOD and GPx levels were lower in astaxanthin supplemented group of Karan Fries heifers than control group. The expression of HSP70 and MnSOD genes was down-regulated and Nrf2 was up-regulated in treatment compared to control group. The THI had a positive correlation with oxidative stress markers i.e. antioxidants enzyme (SOD, GPx & Catalase) as well as expression pattern of HSP70, and MnSOD genes. Based on the results of the present study, it can be concluded that astaxanthin (potent antioxidant) supplementation was effective in lowering the stress levels in treatment group by down-regulating the genes related to heat stress. Therefore, astaxanthin can be an effective supplement for ameliorating the adverse effect of heat stress, mainly in heat sensitive livestock species.